(untitled) (Andamios, Revista de Investigación Social, 2015)
This paper presents a discussion on purview of the immigration issue that develops through the participatory mechanisms of different institutions in the governmental, intergovernmental and civil society areas which featured prominently in the consulting, decision making and ideas-formulation processes that addressed the migratory phenomenon in Mexico (highlighting the think tank experts of migration and the Faith-Based Community Organizations). A theoretical analysis of the relational conception of interagency is developed and interpreted as structurally hybrid. This analysis combines material and symbolic practices because it works as an anchor for the political strategies, and it strengthens the rhetoric of dialog, thus creating decision makers and providing imaginary models of the “integrated management of migration”. The discussion presented here is complemented by examining the relation between migrants and the institution “Casa del Migrante” in Chiapas, Mexico —which provides them humanitarian aid—, and by recovering information from the study case, applied at the time of their traffic by the southern border and within the focused groups.